Pemilihan Supplier Rubber Parts Dengan Metode Analytical Hierarchy Process Di PT.XYZ - Dino Rimantho; Fathurohman Fathurohman; Bambang Cahyadi; Sodikun Sodikun (Universitas Katolik Parahyangan, 2017)
In order to facing an increasingly competitive world of manufacturing industry, it is necessary to select appropriate suppliers to produce quality products at competitive prices. This requires producers to make efficiency. Supplier selection is one way to make efficiency by considering several factors. In this research, the ideal supplier selection is made on rubber component using AHP (Analytic Hierarchy Process) method with three criteria factors that are considered important by the company such as, production factor (48%), quality (40%), and price (12%). Furthermore, this study shows The TRHI as suppliers with the largest value of 51.6% compared to other suppliers such as IKP (24.8%) and IRC (23.6%).